Exchange rates and trade balance in West African economy and monetary union countries: does the content of the traded goods matter? - Camille Detondji Guidime; Adama Diaw; Barthélémy Biao (Cogent Economics & Finance, 2024)
This paper analyzes the role of the nature of traded goods in the effect of the real exchange rate on the trade balance in West African Economy and Monetary Union countries. Empirically, the estimation of the parameters of a distributed lag autoregressive model using the technique of dynamic common correlation estimators is carried out. The results show that, firstly, the low level of intra-industry trade comfort positive real exchange rate effect on trade balance. However, WAEMU countries export raw materials used by their foreign trading partners to manufacture products, which WAEMU countries import in turn; but the raw materials percentage used in the manufacture of those products is negligible to have a beneficial impact on trade balance. Secondly, foreign income levels are less favorable to the countries' balance of trade, as partners have a preference for increasingly sophisticated goods that WAEMU countries do not produce. In terms of economic policy implications, a currency devaluation would have an expected positive effect if trade policy would encourage the consumption of goods and services containing, in their manufacturing process, a significant quantity of their exported products. This article contributes to the existing economic literature by taking into account the characteristics of traded goods in the analysis of the influence of the real exchange rate on the trade balance. A low content of exported goods in the manufacturing process of imported goods from a less advanced country could limit the rebalancing of its trade balance following a change in the real exchange rate. The importance of this research is to empirically show the significant role of the quantity of domestic goods contained in the manufacture of imported goods in studying the relationship between exchange rate changes and the trade balance. The implementation of a specific trade policy coupled with an exchange rate policy in favour of the transformation of primary products into semi-manufactured goods is important for the economy of WAEMU countries.
Keywords: C23; F10; F31; 055; 330; ARDL model; nature of goods exchanged; Real exchange rate; trade balance; WAEMU countries